Faktor Yang Berhubungan Dengan Gangguan Pendengaran Pada Tenaga Kerja - Wahyudin Wahyudin; Bayu Sela Priyatna; Delia Amelia (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Noise can affect a person's hearing quality if exposed continuously. Based on the preliminary study at PLTU X conducted in May 2025, it is known that some locations have noise intensity that exceeds the threshold value, especially in the Boiler engine section which reaches 96.6 dBA and Turbine reaches 103.9 dBA. This study aims to determine the relationship between age, working time, noise exposure and personal protective equipment with hearing loss at PT. PLTU X. This study uses the method used in this study is analytic with a Cross Sectional approach. The population in this study were all workers in the boiler and turbine area of the Indramayu PLTU which amounted to 120, the sample in this study was calculated using the slovin formula with the results of 92 respondents using accidental sampling technique. Data analysis using univariate and bivariate analysis with test chi-square statistical tests. This study shows that there is a significant relationship between tenure and hearing loss. While the variables of age, working time, noise exposure and APD have no relationship with hearing loss. Almost all boiler and turbine area workers have unrisked age, most boiler and turbine area workers have unrisked length of service, all boiler and turbine area workers have unrisked working time, all boiler and turbine area workers have unrisked noise exposure, all boiler and turbine area workers have unrisked APD use